Pengaruh Model Pembelajaran Talking Stik Terhadap Hasl Belajar Siswa Pada Pembelajaran Ips Di Kelas VII SMP Negeri 8 Pematang Siantar T.A 2022/2023 - Erwis Sinaga; Tumpal Manahara Siahaan; Sotarduga Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The researcher's aim was to find out whether there were differences in learning outcomes in social studies learning materials using the Talking Stick learning model for class VIII at SMP Negeri 8 Pematang Siantar. This type of research is quantitative. The population in this study were all students in class VIII of SMP Negeri 8 Pematang Siantar with a total of 288 students. The sample in this study consisted of 2 classes, namely classes VIII-2 and VIII-3 with a total of 64 students out of a total of 288 students. Based on the results of descriptive data analysis, it shows that student learning outcomes in the experimental class (VIII-3) obtained an increase in learning outcomes of 27,5 with an average pretest score = 52,81 and an average posttest score = 80,31. Meanwhile, in the control class (VIII-2), an increase in learning outcomes was obtained by = 11,87 with an average pretest score = 40,94 and an average posttest score = 52.81. This means that there is a significant difference between the improvement in learning outcomes for class VIII-3 students using the Talking Stick learning model and class VIII-2 who learn using conventional learning media. The results of inferential statistics using SPSS version 25 obtained a significance level of 5% or = 0.05. The obtained tcount is 4.979. So it is known that thit>ttab (4.979 > 1.999), which means the alternative hypothesis is accepted It can be concluded that applying the Talking Stick learning model can improve social studies learning outcomes at SMP Negeri 8 Pematang Siantar for the 2022 – 2023 Academic Year.